Inequality patterns in western-type democracies: Cross-country differences and time changes - Andrea Brandolini; Timothy M. Smeeding (Luxembourg Income Study (LIS), 2007)
This paper compares levels and trends in income inequality in industrialized nations. In the mid-1990s, the United States had the highest overall level of inequality of any rich OECD nation, while Northern and Central European countries had the lowest levels. Using a variety of national sources, no common trend is observed in the last quarter of a century. The inequality of disposable incomes increased in the United States and the United Kingdom in the 1980s, and in Sweden and Finland in the 1990s; it rose somewhat in the late 1990s in Canada and the Federal Republic of Germany, but it showed no persistently upward trend in the Netherlands, France and Italy. The paper shows the importance of public redistribution in determining the inequality of disposable income.
Keywords: 330; Einkommensverteilung; Verteilungsgerechtigkeit; OECD-Staaten